Editorial - Gutiérrez Santana, Lucila (Interpretextos revista semestral de creación y divulgación de las humanidades (Colima), 2025)
In these times, characterized by the speed at which discourses change, the vertigo produced by countless screens and the dispersion of all kinds of links, Interpretextos presents itself as a platform where critical, aesthetic, and analytical perspectives from various disciplines converge, sharing the desire to understand—and narrate—the complexity of our time. This fourth issue brings together contributions from fields such as literature, linguistics, journalism, cultural studies, and communication, with the firm intention of weaving together intellectual networks that serve to sustain the conversation around art, thought, and social life. This issue of our magazine proposes a diverse map of contemporary concerns that, like communicating vessels, allow us to reflect on who we are, what we remember, and what we imagine as the future.